2003
DOI: 10.1037/0002-9432.73.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Homicidality in schizophrenia: A replication study.

Abstract: This study attempted to replicate the results of R. C. Schwartz, S. Petersen, and J. L. Skaggs (2001) by testing predictors of homicidality in a new sample of participants with schizophrenia. Results of multiple regression analyses showed that manic symptoms and substance abuse were significantly positively correlated with more extreme homicidality. Global Assessment of Functioning scale ratings were significantly negatively correlated with ratings on homicidality. Finally, men displayed significantly heighten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…30 The authors found that manic symptoms, psychotic symptoms and impaired global function all correlated significantly with homicidal ideation and attempted murder, lending credence to the supposition that the lack of reality testing, judgment and communication, as well as impairment in other functional areas, can lead to violent or homicidal behavior.…”
Section: Schizophrenia Schizoaffective Disorder and Delusional Disordermentioning
confidence: 94%
“…30 The authors found that manic symptoms, psychotic symptoms and impaired global function all correlated significantly with homicidal ideation and attempted murder, lending credence to the supposition that the lack of reality testing, judgment and communication, as well as impairment in other functional areas, can lead to violent or homicidal behavior.…”
Section: Schizophrenia Schizoaffective Disorder and Delusional Disordermentioning
confidence: 94%
“…In our study, male gender, young age, illness duration and delusional beliefs were the main determinants and triggers of homicide in both schizophrenic and bipolar disorder patients. In a similar study by Schwartz et al [16], manic symptoms and substance misuse were significantly correlated with more extreme homicidality. They also showed that men displayed significantly heightened homicidality than women.…”
Section: Discussionmentioning
confidence: 65%
“…Recent literature suggests that psychosis is related to higher incidence of violence than that found in the general public (Schwartz, Petersen, Reynolds, & Austin, 2003;Schwartz, Petersen, & Skaggs, 2001). Schwartz et al (2003) recommended that clinicians ''pay particular attention to evaluating homicidality in patients who are male, have schizophrenia, who abuse substances, who show acute manic symptoms, and whose global functioning has recently declined'' (p. 74). As with the suicide assessment, the crisis worker should assess for ideation, intent, and plan to harm others.…”
Section: Case Study: Rolandomentioning
confidence: 99%